Specialized fitness trainer business mix for the elderly in Thailand (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to 1. To study the exercise behavior of the elderly in Thailand. 2. To study the relationship between personal factors and the marketing mix of a specialized fitness trainer business for the elderly in Thailand and 3. To study the marketing mix of a specialized fitness trainer business for the elderly in Thailand. Sample selection by hierarchical random sampling (Stratified sampling) according to the proportion of population in each region get all samples 400 people. Tools used for research was a questionnaire. Statistics used were percentages Mean and Frequency. The results showed that the elderly use fitness services for exercise. 1–3time day per week 42.6 percentage and exercise 1-2 hours per time 60.4 percentage. Frequency of using fitness services in 1 month ago is More 7 times, calculated as an 84.5 percentage. And a way to know information about using fitness services from online media such as Facebook 56.3 percent. The ingredients for a specialized fitness trainer business for the elderly in the country are overlooked every time. The relationship between personal factors and the marketing mix of specialized fitness trainers for the elderly in Thailand depending on age. education level, occupation, and average monthly income.